Availability of water resources in the río Bermúdez micro-basin. Central Region of Costa Rica - Hernando Echevarría, Ligia; Orozco Montoya, Ricardo (Observatorio Medioambiental, 2015)
The Rio Bermúdez micro-basin makes up part of the principal hydrological resource area in the Central Region of Costa Rica. For this reason a study was done to determine the availability of hydrological resources in said micro-basin to identify areas with potential water availability problems. A monthly water balance was calculated using land use, geomorphology and climate parameters. From these water balance studies, the amount of available water was calculated and classified into four categories, however, in this micro-basin, only three categories were identified: high, medium and moderate water availability. No areas were identified with low water availability, indicating availability is sufficient; however, there is increasing demand on water resources because over half of the micro-basin area is classified as having moderate water availability.
Keywords: Water balance; watershed basin; water resource availability.